Ceramic sealing parts and manufacturing method thereof
Patent Information
- Application Number
- JP2023086569
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-05-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-05-26
Smart Images

Figure 0007631412000004 
Figure 0007631412000005 
Figure 0007631412000006
Abstract
Description
[Technical field]
[0001] The embodiment is generally a joint between ceramic parts and metal parts used in electric power pipes, etc. This invention relates to ceramic sealed parts (hereinafter referred to as ceramic sealed parts). [Background technology]
[0002] Molybdenum (Mo) and other ceramic sealing parts for magnetrons, power tubes, and electron tubes The metallization layer, which is mainly composed of a high melting point metal, is made of alumina (aluminum oxide: AlO 3) and other ceramic parts are used. The ceramic and metal sealing parts are bonded together to block the outside air and hermetically seal the inside of the parts. This makes it possible to protect the inside from the external environment and provide electrical insulation with ceramics. For example, a ceramic sealing part with the shape shown in Figure 1 is made of alumina sintered body. The rings on the upper and lower end surfaces of the cylindrical ceramic part are made of molybdenum. The metallized layer is formed on the surface of the metallized layer. A nickel (Ni) layer of a certain thickness is formed to improve the bonding strength with the metal and perform sealing. This nickel part and the cylindrical metal part are joined by silver solder (e.g. BAg-8). is.
[0003] As a ceramic sealing part, a ceramic cylinder is formed with a metal surface of molybdenum and then bonded to iron. An electron tube having a vacuum airtight structure in which a metal cylinder is joined with a brazing material is disclosed (Patent According to Patent Document 1, by replacing the metal cylinder with iron instead of Kovar, It is possible to manufacture electron tubes of low cost.
[0004] In addition, nickel is added to ceramics by using active metals without using high melting point metals such as molybdenum. Patent Document 2 discloses a vacuum switch outer tube made of a ferroelectric alloy. This allows for a vacuum switch with high bonding strength without creating intermetallic compounds that cause instability in the bonded state. It is possible to manufacture a tubular outer tube. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Application No. 1-46978 [Patent Document 2] JP 2001-220253 A Summary of the Invention [Problem to be solved by the invention]
[0006] When metallizing the ceramic surface with a high melting point metal such as molybdenum, A furnace is required to heat the material to a high temperature of over 400°C, and energy is required to process the material at high temperatures. In addition, the metal parts were left with the high melting point metallization layer. It is difficult to solder to the metal, and the surface needs to be plated with nickel or other metals, which makes the process complicated. It was complicated.
[0007] In order to ensure sealing (airtightness) when joining active metal brazing materials, a certain joining width is necessary. The thermal expansion coefficients of ceramics and metals are different (for example, the thermal expansion coefficient of alumina is 7.2×10 -6 / ℃ compared to copper 16.5×10-6 / ℃, iron 11.7×10-6 / ℃) The active metal brazing is more likely to cause cracks. In comparison, bonding is performed at a low temperature of 850°C, making it possible to alleviate the difference in thermal expansion. When joining metal parts using metal brazing material or silver brazing material, high temperatures are required to increase the joining strength. However, if the joining temperature is increased, the silver and copper in the silver solder will melt. There was a possibility that the ceramic parts would separate and the bonding strength with the ceramic parts would decrease.
[0008] In addition, when joining metal parts using active metal brazing material, use active metal brazing material paste. Brazing is used to form a bonding layer with ceramics and then bond it to metal using a brazing material. In the past, the active metal brazing material was used to form a joint layer at a higher temperature than in the past. The melting point of the active metal brazing paste was higher than that of the brazing material. To increase the melting point, it is necessary to add a large amount of metals with high melting points such as copper (Cu) or silver (Ag). During the heating process, the brazing material was in a state where it was likely to melt and separate from the other brazing material metal components. This can cause uneven soldering and lead to leaks and cracks. The material is often processed into foil shapes, etc., and in the case of small-lot, high-mix production, it is necessary to process the brazing material parts many times. This was essential and caused costs.
[0009] The embodiment solves such a problem, and is a method for bonding ceramic parts with an active metal brazing material. This highly productive ceramic bonding method suppresses bonding failures and leak failures when bonding ceramic and metal parts. The present invention relates to a sealing part and a manufacturing method thereof. [Means for solving the problem]
[0010] The ceramic part and the metal part according to the embodiment are bonded with a bonding layer containing silver, copper, and an active metal. In the bonded ceramic sealed parts, silver and copper are fused in the bonding layer. The ceramics of the bonding layer are divided into 20 or more layers and the mass percentages of silver, copper, and active metal are measured. When the mass% of active metal is plotted from the part side to the metal part side, the maximum value of the mass% (Wm) There are maximum values for copper mass% (Wc) and silver mass% (Wa). The second largest maximum value of copper mass% is 0.7 times or less than the maximum value (Wm), and the minimum value of copper mass% The value is 0.3 times or more the maximum value (Wc), and the mass percent of silver up to 1 / 4 of the ceramic part side The maximum value of is between 0.3 and 0.5 times the maximum value (Wa).
[0011] In addition, in the ceramic sealed part of the embodiment, in the plot of copper mass%, 0.5Wc The following range is 40% or less, and the range of 0.5Wa or less is 5% in the silver mass plot. It is less than 0%.
[0012] In the ceramic sealing part of the embodiment, the active metal brazing material is titanium, zirconium , hafnium, and one or more active metals selected from copper and silver. The material is metal.
[0013] In the ceramic sealed component of the embodiment, the bonding layer has a thickness of 70 μm or more.
[0014] In the ceramic sealing part of the embodiment, the metal part is iron or an iron alloy, iron-nickel based alloys, or copper or copper alloys.
[0015] In the ceramic sealing component of the embodiment, the ceramic component is made of alumina.
[0016] Also, a method for manufacturing a ceramic sealing part for joining a ceramic part and a metal part according to the embodiment is provided. In this method, a paste made of active metal brazing material containing copper is printed on ceramic parts, dried, and heated. Then, an active brazing metal layer is formed on the end surface of the ceramic part, and silver is applied to the active brazing metal layer. After printing and drying the paste made of brazing material containing A bonding layer is formed to bond the ceramic and metal parts.
[0017] Also, a method for manufacturing a ceramic sealing part for joining a ceramic part and a metal part according to the embodiment is provided. In the method, the heating temperature (T1) of the active metal brazing material layer is 800° C. or less, and the brazing material layer The heating temperature (T2) is 820°C or less, and the difference in heating temperature (T2-T1) is 20°C or more. be.
[0018] Also, a method for manufacturing a ceramic sealing part for joining a ceramic part and a metal part according to the embodiment is provided. In this method, the printing thickness of the paste made of active metal brazing material is 20 μm or more, and the filler material containing silver is The thickness of the paste made of the filler material is 50 μm or more.
[0019] Also, a method for manufacturing a ceramic sealing part for joining a ceramic part and a metal part according to the embodiment is provided. In this method, a solder containing silver is applied to the entire surface of an active metal solder layer. Print the list. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a perspective view showing an example of a ceramic sealing component according to an embodiment; [Diagram 2] FIG. 1 is a cross-sectional view of a ceramic sealing component according to an embodiment of the present invention; [Diagram 3] FIG. 1 is a cross-sectional view showing an example of a joint portion of a ceramic sealing component according to an embodiment; [Figure 4] FIG. 1 is a diagram showing an example of a manufacturing process for a ceramic sealing component according to an embodiment. [Diagram 5]FIG. 1 is an enlarged view of an example of a cross section of a joint of a ceramic sealed component according to an embodiment; [Figure 6] FIG. 1 is a diagram showing a mass percentage of an example of a cross section of a joint of a ceramic sealing component according to an embodiment. [Figure 7] FIG. 1 is a diagram showing a mass percentage of an example of a cross section of a joint of a ceramic sealing part according to a comparative example. [Figure 8] FIG. 1 is a diagram showing a mass percentage of an example of a cross section of a joint of a ceramic sealing part according to a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The ceramic part and the metal part according to the embodiment are bonded with a bonding layer containing silver, copper, and an active metal. In the bonded ceramic sealed parts, silver and copper are fused in the bonding layer. The ceramics of the bonding layer are divided into 20 or more layers and the mass percentages of silver, copper, and active metal are measured. When the mass% of active metal is plotted from the part side to the metal part side, the maximum value of the mass% (Wm) There are maximum values for copper mass% (Wc) and silver mass% (Wa). The second largest maximum value of copper mass% is 0.7 times or less than the maximum value (Wm), and the minimum value of copper mass% The value is 0.3 times or more the maximum value (Wc), and the mass percent of silver up to 1 / 4 of the ceramic part side The maximum value of is 0.3 to 0.5 times the maximum value (Wa).
[0022] In addition, the present invention relates to a method for manufacturing a ceramic sealing part for joining a ceramic part and a metal part according to an embodiment of the present invention. The method involves printing and drying a paste made of an active metal brazing material containing copper onto a ceramic part. The end surface of the ceramic part is heated to form an active metal brazing material layer, and the active metal brazing material layer is After printing and drying a paste made of solder containing silver, metal parts are placed and heat treated. A brazing material layer is formed to join the ceramic and metal parts.
[0023] FIG. 1 shows an example of a perspective view of a ceramic sealing part 1 according to an embodiment. The ceramic part 2 is a cylindrical metal part. In FIG. 1, the upper part of the ceramic part 3 is This shows an example in which a metal part 2 is joined to the side end surface and the lower (opposite) end surface. The shape is not limited to this, and may be a square cylindrical ceramic part or a metal part. The lower part is a ceramic part and only the upper part (one side) is joined to a metal part. Metal parts may be joined to ceramic parts having two or more openings on one side. Let us assume that.
[0024] In the ceramic sealing part 1 according to the embodiment, for example, the ceramic part 3 has a cylindrical shape. A ceramic part made of alumina and a metal plate provided on a part of the surface of the ceramic part. The bonding layer here is made of copper (Cu) on the ceramic part side, Metals such as silver (Ag) and titanium (Ti), zirconium (Zr), and hafnium ( For example, the metal part 2 is a mixture of Kovar ( It is a cylindrical metal part made of Fe-Ni-Co or copper (Cu).
[0025] FIG. 2 shows an example of a cross-sectional view of a ceramic sealing part according to an embodiment. The sealing part is 2, the metal part is 3, and the ceramic part is 4. The ceramic part 3 is made of aluminum. One of the following: alumina, aluminum nitride, silicon nitride, or zirconia-added alumina (argil) It is preferable that the alumina is an alumina having other ceramics added thereto. Zirconia-added alumina is a mixture of alumina and zirconium oxide. In addition, sintering aids other than zirconia are added to alumina. This is because the sintering aid added forms a grain boundary phase made of a glass phase, resulting in a sintered alumina body. The sintering aids are manganese (Mn), silicon (Si), magnesium (Mg), and These include compounds of Mn, Si, At least one of Mg and Ca is added at a total of 1 to 15 mass% in terms of single metal element. In addition, ceramic parts have good cost performance as insulating and sealing parts. A fine alumina is preferred.
[0026] The materials of the metal part 2 to be joined with the ceramic part 3 are iron (Fe) and iron alloys, iron-nickel Kel-based alloys, copper (Cu) and copper alloys, tungsten (W), and molybdenum (Mo). The iron alloy includes carbon steel such as rolled steel, and alloy steel such as chromium steel. Nickel-based alloys include 42 alloy (Ni 42 mass%, Mn 0.8 mass% or less, balance Fe), Bar (Ni 29 mass%, Co 17 mass%, Fe balance) and others. Iron and iron alloys have excellent thermal expansion coefficients and other physical properties. is an iron-nickel alloy. It is also prone to deformation in order to relieve stress caused by the difference in thermal expansion. The metal parts are made of copper and copper alloys, and when the heat effect is large, copper and copper alloys are used. The copper alloy may be oxygen-free copper, tough pitch copper, deoxidized copper, or other pure copper, or a base metal. For this reason, depending on the application, iron and iron alloys are also used. It is preferred to form the metal parts from alloys, iron-nickel based alloys, copper and copper alloys. In addition, metal parts must be made of two or more different metals, such as Kovar on one side and copper on the other. Metal parts can be manufactured by pressing, cutting, bending, etc. In addition, nickel is added to improve corrosion resistance and wettability. It is possible to perform plating such as plating of gold.
[0027] FIG. 3(a) is an enlarged view of part A in FIG. 2. In Fig. 3(a), the tip of the metal part is bent and flattened through the bonding layer. The ceramic part is joined to the ceramic part at the surface. The tip of the metal part is joined to the ceramic part in a line (end face) in the circumferential direction via a joining layer. is doing.
[0028] The joint is made at low temperature by using a brazing material containing an active metal that easily wets the ceramics. To prevent the loss of strength caused by the dissolution of silver and copper, a more cost-effective layer is formed. We select copper with good performance and add low melting point tin (Sn) to lower the melting point of copper. In addition, the active metal in the active metal brazing layer reacts with hydrogen and becomes embrittled, causing leakage defects. Therefore, it is recommended to print the active metal brazing layer with silver brazing paste and then heat it in a nitrogen / hydrogen atmosphere. Metal parts are joined by heating in air. If the heating temperature is too high, the silver solder will The temperature should be set to 50°C below the brazing temperature, as too much silver would diffuse into the active brazing metal layer. Also, if the heating temperature is too low, the brazing paste will not wet the active metal brazing material layer, and the brazing will not occur. Set the application temperature to +20℃ or higher.
[0029] Active metal brazing material 4The brazing material is made of an active metal such as Ti (titanium). Examples of active metals other than Ti include Zr (zirconium) and Hf (hafnium). An example of the active brazing material is a mixture of Ti and copper (Cu). For example, Ti is 0.1 to 10 mass%, and Cu is the remainder. Another example of the active brazing material is a mixture of Ti, Ag, and Cu. Ti is 0.1 to 10 mass%, Cu is 10 to 60 mass%, and Ag is the remainder. In addition, in order to control the diffusion of the active brazing material during bonding, 1 to 15 mass% of one or more selected from indium (In), tin (Sn), aluminum (Al), silicon (Si), carbon (C), and magnesium (Mg) may be added. The active brazing material paste is printed on the surface of the ceramic part and then dried. Thereafter, the ceramic part is heated at 750 to 800°C in a vacuum or in a non-oxidizing gas to form a metallized layer (bonding layer) on the surface of the ceramic part. Next, a silver brazing paste is printed on the surface of the metallized layer and then dried. After that, a metal part is placed so that it is in contact with the printed and dried paste surface, and the ceramic part and the metal part are joined by heating at 780 to 820°C in a vacuum or in a non-oxidizing gas.
[0030] FIG. 4 shows a process diagram of the manufacturing method of the ceramic sealing component according to the embodiment shown in FIG. 4(a) is a cross-sectional view of the ceramic part 3. In FIG. 4(a), the ceramic part 3 has a surface on the outer periphery and the inner periphery. The chamfer is formed. It is possible to use the product without the chamfer, but it is recommended to use the product without the chamfer. The end faces of parts are easily chipped due to external impacts, so this is an effective way to prevent chipping. (b) After printing and drying the active metal brazing paste on the ceramic part 3, the ceramic part 3 is vacuum- or non-oxidized. The ceramic substrate is heated in a chlorine gas to form an active brazing metal layer 4. Since the paste is printed on the end surface of the component, the surface of the active metal brazing material layer 4 before bonding is approximately flat. In addition, in Fig. 4(b), the active metal brazing paste is printed only on the flat surface of the end. However, it is also possible to print the active metal brazing material even on the chamfered portion.
[0031] FIG. 4(c) shows the state where the brazing paste 6 is printed and dried on the surface of the joining layer. The brazing paste contains active metals that are susceptible to hydrogen embrittlement. It is preferable that the paste cover the entire surface of the active metal brazing material. When the same print pattern as the brazing paste is printed on top of the brazing paste, the viscosity of the brazing paste is activated. By making the viscosity slightly lower than that of the metal paste, it is possible to spread and cover the entire surface during printing. In addition, the active metal is removed by printing patterns that are larger (wider) than the printing patterns of the brazing paste. It is also possible to print so as to cover the entire surface of the metal brazing layer. When heated, the brazing paste does not react with the ceramic parts and forms an active metal brazing layer or a metal part. At this time, they form lumps around the active metal brazing material layer and metal parts. This causes stress concentration. For this reason, when the printing pattern of the brazing paste is large, It is preferable to make the pattern 0.1 mm or less larger than the printed pattern of the active metal brazing paste. stomach.
[0032] FIG. 4(d) shows the state in which the metal part 2 is placed on the surface of the printed and dried brazing paste 6. When joining multiple metal parts 2 as shown in Figure 2, they are placed at the same time. The metal parts 2 are joined together.
[0033] FIG. 4(e) shows the state where the metal part 2 is joined. The brazing material layer 5 creeps up onto the side surface of the metal part 2. In this way, the brazing material layer 5 covers the metal part 2, forming a strong bond. This enables leak-free sealing inside and outside the component.
[0034] Next, a method for manufacturing a ceramic sealed component according to an embodiment will be described. As long as the sealing part has the above-mentioned configuration, the manufacturing method thereof is not particularly limited. The following methods can be used to obtain a high yield.
[0035] An example of a ceramic part according to the embodiment is a circle. tube The shape is, for example, an outer diameter of 50 mm, an inner diameter of 38 mm, and a height of 50 mm. Ceramic parts are prone to chipping and cracking at the corners due to external impacts. For this reason, it is preferable to chamfer the outer and inner periphery of the end face. The chamfer shape can be, for example, C chamfer or R chamfer, and the chamfer size is preferably 0.1 to 2 mm.
[0036] The materials of the metal parts according to the embodiment are iron and iron alloys, copper and copper alloys, 42 alloy and edge Examples include iron-nickel alloys such as tungsten and molybdenum. Kovar has excellent physical properties such as number of layers, and is used to relieve stress caused by differences in thermal expansion. Copper and copper alloys are easily deformed. For this reason, metals made of Kovar, copper and copper alloys are It is preferred to form a metal part.
[0037] An example of the shape of the metal part according to the embodiment is a substantially cylindrical shape. For example, the height is 20 mm. In the case of Fig. 3(a), the unprocessed part has an outer diameter of 48 mm and an inner diameter of 46 mm. The tip is a flange shape that is bent inward almost vertically and is 4 mm long. Metal parts are pressed into a cylindrical shape, and then the tip is pressed or drawn. The flange shape is made by pressing the bottomed cylinder with a press, leaving the bent part. It is also possible to obtain a bent shape by bending the wire. In the case of Fig. 3(b), the outer diameter is 46 mm and the inner diameter is 4 These metal parts are plated with nickel or other metals to improve corrosion resistance and wettability. It is possible to do the following.
[0038] The active metal brazing material and brazing material are in the form of paste. The sheets and wires are active metal brazing materials. The material is melted and processed into a sheet or wire shape, and then cut to the required dimensions to fit the product shape. In contrast, the paste requires no process for manufacturing the paste. However, it is easy to handle as it can be printed on the necessary parts according to the product shape. If the amount of active metal brazing material is too small, the brazing material will break and the brazing material will break. Accumulation can occur, which can cause stress fracture. Therefore, the active metal filter to be used should be adjusted according to the brazing area. The amount of the cavity can be adjusted.
[0039] The active metal brazing paste is a mixture of active metal powder and brazing metal powder, and is then coated with organic bimetallic compound. The organic binder is used in the drying and bonding (heating) processes. There are no particular limitations as long as it is burnt more easily. A preferred example is ethyl acetate. Organic solvents are particularly suitable if they are burned away during the drying or baking process. Preferred examples include, but are not limited to, terpineol and butyl carbitol. The active metal brazing paste can be prepared by, for example, crushing active metal powder and brazing metal powder. After mixing, the mixture is mixed with an organic binder and an organic solvent. The ratio of the active metal contained in the active metal brazing material component is 0.1 to 15 mass%, preferably 0.5 ~10% by mass.
[0040] The printing thickness of the active metal brazing paste is preferably 20 to 100 μm. If the printing thickness is less than 20 μm, the thickness of the active metal brazing layer will vary, reducing the joining strength. On the other hand, if it exceeds 100 μm, no further effect will be obtained. The paste is printed in a uniform thickness on the end faces of the ceramic parts by a method such as screen printing. If the printing thickness is not uniform, there will be an excess of active metal brazing material in thick areas, causing brazing material to accumulate and cracks to occur due to thermal stress. Also, in thin areas, the active metal brazing material will be too thick, causing the brazing material to accumulate and cracks to occur due to thermal stress. genus Brazing material shortage will cause leaks, so it is preferable that the difference in printing thickness between the thick and thin parts be 15 μm or less, and more preferably 10 μm or less.
[0041] The paste printed on the ceramic parts is dried in the air. The drying temperature is low and the If the drying time is too short, the solution components of the paste will not evaporate sufficiently, which may cause voids during bonding. Conversely, if the drying temperature is high and the drying time is long, the paste surface will become oxidized. Therefore, the drying temperature is set to 50 to 100°C, preferably The drying temperature is 60 to 80° C. The drying time is 5 to 30 minutes, and preferably 10 to 20 minutes.
[0042] After the paste is dried, the metal parts are placed on the dried paste surface and heated to bond them. The bonding temperature is 600 to 850°C, preferably 700 to 800°C. The bonding time is preferably in the range of 5 to 60 minutes after the bonding temperature is reached. If the bonding temperature is low and the bonding time is short, the active metal brazing material may not melt sufficiently and bonding may not occur. Conversely, if the bonding temperature is high and the bonding time is long, the active metal brazing material may melt too much and spread, causing voids. The active metal bonding atmosphere may be in a vacuum or a non-oxidizing atmosphere as necessary. When performing in a vacuum, a 1×10 -2Pa or less. Examples of the non-oxidizing atmosphere include a nitrogen atmosphere and an argon atmosphere. By using a vacuum or a non-oxidizing atmosphere, the active metal brazing material layer can be prevented from being oxidized. This improves the bonding strength. A continuous furnace or a batch furnace is used for brazing. A continuous furnace is superior in terms of mass production, while a batch furnace allows easy control of temperature and atmosphere. The active metal brazing material layer is formed by heating for a predetermined time in the above atmosphere.
[0043] The brazing paste is made up of metal parts and active brazing metal, and metals that have good wettability. The brazing material most often used to join laminates and metal parts is silver brazing. Silver brazing is a material made of silver and copper. It is mainly composed of , but may contain other metals such as zinc and nickel. Silver brazing filler metal (BAg-8) is often used to join metal parts to metal objects. ) is used in BAg-8 according to "Silver solder (JIS Z3261:1998)". g) 71-73%, copper (Cu) 27-29%, and the total of other elements is 0.15% or less. The brazing paste is made by mixing brazing metal powder with an organic binder and an organic solvent. The organic binder is burned away during the drying and bonding (heating) processes. There is no particular limitation. A preferred example is ethyl cellulose. The organic solvent is not particularly limited as long as it is burned off during the drying and baking steps. Preferred examples include terpineol and butyl carbitol. For example, metal powder is crushed and mixed, then mixed with an organic binder and an organic solvent to prepare the powder. This was done.
[0044] The printing thickness of the brazing paste is preferably 50 to 200 μm. If the printing thickness is less than 50 μm, the thickness of the brazing paste layer will vary, reducing the joining strength. On the other hand, if it exceeds 200 μm, no further effect will be obtained. The paste is printed in a uniform thickness on the end faces of the ceramic parts by a method such as screen printing. If the printing thickness is not uniform, there will be an excess of brazing paste in the thick parts, causing brazing paste pools and cracks due to thermal stress. Also, in the thinner parts, the active metal genus A lack of brazing material can cause leaks, so it is preferable that the difference in printing thickness between the thick and thin parts be 20 μm or less, and more preferably 15 μm or less.
[0045] The brazing paste printed on the active metal brazing layer is dried in air or the like. If the temperature is low and the drying time is short, the solution components of the paste will not evaporate sufficiently, resulting in voids during bonding. Conversely, if the drying temperature is high and the drying time is long, the surface of the paste may become dirty. Oxidation may progress and the bonding temperature conditions may change. For this reason, the drying temperature should be set to 50 to 100 The drying temperature is 5 to 30 minutes, preferably 10 to 20 minutes. It is 0 minutes.
[0046] After the brazing paste has dried, the metal parts are placed on the dried paste surface and heated to join them. The bonding temperature is 650 to 900°C, preferably 750 to 820°C. The time is preferably in the range of 5 to 60 minutes after the bonding temperature is reached. As shown in Fig. 1, the brazing material layer 5 melts and spreads over the surface of the metal part 2, forming a bond. When the joining temperature is low and the joining time is short, the active metal brazing material does not melt sufficiently. Conversely, if the joining temperature is high and the joining time is long, the brazing material may not be bonded properly. If the material melts too much, it may spread out and cause solder cracks or voids.
[0047] In addition, the brazing and joining atmosphere shall be a non-oxidizing atmosphere as necessary. The atmosphere can be a nitrogen atmosphere or a hydrogen nitrogen atmosphere. This can prevent the layer from being oxidized, thereby improving the bonding strength. The furnaces used for brazing are continuous furnaces and batch furnaces. The temperature and atmosphere are easily controlled in a batch furnace. Brazing is performed by heating for a fixed period of time.
[0048] The thickness of the bonding layer that bonds the ceramic part and the metal part is preferably 70 μm or more. As mentioned above, the bonding layer is made up of an active metal brazing material layer of 20 μm or more and a brazing material layer of 50 μm or more. The thickness of the bonding layer is the thickness of the bonding surface of the metal part and the ceramic part. For example, in Fig. 3(a), the tip of metal part 2 is a flange-shaped The bent part is bent in a shape similar to that of the ceramic part 3, and is joined to the ceramic part 3 at a flat surface. The thickness of the bonding layer is approximately the center of the metal part 2. Therefore, the thickness of the joining layer is set to approximately the center of the end surface of the metal part 2. Furthermore, if the tip of the metal part 2 is sharp, such as U-shaped or V-shaped, The thickness of the bonding layer is the tip part where the wire is bonded.
[0049] Figure 5 shows an enlarged view of part B in Figure 3(b). In Figure 5, the gap between the ceramic and metal parts is 20 The divided state is shown diagrammatically. Energy dispersive X-ray fluorescence analysis was performed for each divided part. The mass percentage of the constituent elements is measured using an EDX device. When the mass% of active metal is plotted from the product side to the metal part side, the maximum value of the mass% of active metal (Wm) is There are two maximum values for copper mass percentage (Wc) and silver mass percentage (Wa). If there are more than two, the larger value is taken as the maximum value.
[0050] In one example of a ceramic sealed component according to the embodiment, the central 200 μm of the joint cross section The specimen was divided into 3.6 μm sections (height) and analyzed by an energy dispersive X-ray fluorescence analyzer (EDX). The mass percentage of the constituent elements is measured. The mass percentages of elements in an example of a joint cross section are plotted in Fig. 6. (a) Titanium ( (b) copper (Cu), and (c) silver (Ag) from the ceramic side to the metal side, respectively. The mass percentage (wt%) values of the points (distances) are plotted. For example, values from 0 to 3.6 μm are plotted at 0 μm on the X-axis.
[0051] In Figure 6, the second largest maximum value of active metal mass% (Wm2) is 6.0 mass% ( Wm) is 0.49 times 12.2 mass%, which is less than 0.7 times. When the active metal is bonded to the ceramic, it reacts with the ceramic to form a bonding layer. When the solder paste is printed and heated (heating temperature (T2)), A part of the active metal diffuses into the brazing material layer. At this time, if the heating temperature (T2) is low, the active metal The effect on the metal bonding layer is small, so the effect on the maximum value is small. When 2) is high, the active metal layer of the brazing material layer is largely diffused, and the active metal in the brazing material layer is The maximum value becomes greater than 0.7 times the maximum value (mass). At this time, the active metal required for joining If it is insufficient, the bonding strength decreases.
[0052] In Figure 6, the minimum value of copper mass% is 21.1 mass% and the maximum value (Wc) is 56.6 mass%. For example, if the brazing filler metal used is BAg-8 brazing filler metal, In some cases, the copper content is 28%, so the active brazing material should not contain more copper than that. When active metal brazing material is used, the copper has a maximum value on the ceramic part side. When 2) is low, the effect on the active metal brazing layer is small, so there is a minimum value as shown in Figure 6. The effect on the magnitude of the maximum value is small, less than 0.3 times. 2) is high, the silver and copper in the brazing material melt and separate, so the value exceeds 50%. If the metal of the filler melts and separates, the joint strength decreases. The smallest value is the minimum value.
[0053] In addition, in Figure 6, the maximum mass percent of silver up to 1 / 4 of the distance on the ceramic part side was 28.7 The mass% and maximum value (Wa) are 0.46 times 63.0 mass%, and the mass% is between 0.3 and 0.5 times. This is a state in which the brazing material containing silver is adequately diffused into the active brazing material layer. If the filler metal is adequately diffused into the active metal brazing layer, the active metal brazing material and the brazing layer will be firmly bonded. It is in a mated state.
[0054] In addition, in the plot of copper mass% in Figure 6, the range of 0.5Wc or less was 6 out of 27 points, or 22.2%. Becoming It is within the range of 40% or less. If the range of 0.5Wc or less is 40% or less, There is enough copper to contribute to bonding and sealing. 0.5W c If the following range exceeds 40%, copper This can cause parts with excess of other constituent elements, resulting in poor bonding and leaks.
[0055] In addition, in Figure 6, 13 out of 27 points in the plot of silver mass% are in the range of 0.5 Wa or less. The percentage of 0.5Wc or less is 40% or less. If the range of 0.5WC or less exceeds 40%, there is sufficient silver to contribute to bonding and sealing. If the amount of silver increases, there will be areas where the constituent elements other than silver are excessive, which can cause poor bonding or leaks.
[0056] FIG. 7 is a plot of mass % when the heating temperature (T2) is low. The second largest maximum value was 4.9 mass%, which is less than 0.7 times the maximum value (Wm) of 9.4 mass%. However, the minimum value of copper mass% was 10.1 mass% and the maximum value (Wc) was 57.3 mass%. This is because there is not enough copper in the bonding layer. This indicates that there is a possibility of joint failure or leakage failure. The maximum mass% of silver up to the 1 / 4 distance from the center was 20.3 mass%, and the maximum value (Wa) was 75.0 mass%. This is because the silver-containing brazing filler metal is not fully embedded in the active metal brazing filler metal layer. If the brazing material is not sufficiently diffused, the active metal brazing material This weakens the bond between the material and the brazing material, causing poor bonding and leaks.
[0057] In addition, in Figure 7, 10 out of 24 points in the copper mass% plot are in the range of 0.5Wc or less. The range of 0.5WC or less exceeds 40%, and the range is 41.1% and outside the range of 40% or less. In addition, there are areas where the constituent elements other than silver are excessive, which can cause poor bonding and leaks. In the mass plot, the range below 0.5 Wa is 13 out of 27 points, or 48.1%. If the range of 0.5Wc or less is 40% or less, it is suitable for bonding and sealing. There is sufficient silver to contribute. If the range of 0.5WC or less exceeds 40%, the components other than silver This causes parts with excess silicon, resulting in poor bonding and leaks.
[0058] Figure 8 is a plot of mass% when the heating temperature (T2) is high. In Figure 8(a), the second largest maximum value of active metal mass% is 12.0 mass% and the maximum value (Wm) is 1 4.1 The mass% values are larger than 0.85 and 0.7 times the mass% values. This indicates that a sufficient amount of active metal cannot form a bonding layer near the surface of the ceramic parts. If there is little active metal that contributes to the bonding of ceramic parts, this can cause bonding failure and leak failure near the ceramic parts. In addition, the minimum mass% value of copper is 3.6 mass%, which is 0.05 times the maximum value (Wc) of 79.2 mass%, which is smaller than 0.3 times. This indicates that there are places in the bonding layer where there is not enough copper, which can cause bonding failure and leak failure. In addition, the maximum mass% value of silver up to 1 / 4 of the ceramic part side is 0.6 mass%, which is 0.01 times the maximum value (Wa) of 86.9 mass%, which is small. This is because the brazing material containing silver is not sufficiently diffused into the active metal brazing material layer. If the brazing material is not sufficiently diffused, the bond between the active metal brazing material and the brazing material will be weak, causing bonding failure and leak failure.
[0059] In addition, in FIG. 8, in the plot of copper mass%, 10 out of 22 points are outside the range of 0.5Wc or less, i.e., 45.5% and 40% or less. c If the range below exceeds 40%, there will be areas where the constituent elements other than copper are excessive, which will cause poor joints and leaks. Also, in the plot of silver mass, 15 out of 22 points, or 68.2%, are outside the range of 50% or less. 0.5W c If the range below exceeds 50%, there will be areas where the constituent elements other than silver are excessive, which will cause poor bonding or leaks.
[0060] According to the method for producing a ceramic sealing part in the embodiment of the present invention, We obtained ceramic sealing parts with excellent cost performance while maintaining the airtight performance of the entire product. It is possible.
[0061] (Examples 1 to 8, Comparative Examples 1 to 8) Alumina was added with the auxiliary agents manganese oxide (MnO2), silicon oxide (silica: SiO2), and magnesium oxide (magnesia: MgO) to prepare granulated powder with a composition of 92 mass% alumina. The granulated powder was molded in a die press and sintered in air at 1500°C to obtain a cylindrical ceramic part with an outer diameter of 50 mm, an inner diameter of 40 mm, a height of 50 mm, an outer diameter C chamfer of 0.5 mm, and an inner diameter C chamfer of 0.5 mm. Aluminum nitride granulated powder was also prepared by adding 3 mass% of yttria (yttrium oxide: Y2O3) auxiliary agent to aluminum nitride (AlN). The granulated powder was molded in a die press and sintered in nitrogen at 1800°C to obtain a cylindrical ceramic part with the same dimensions as the alumina part.
[0062] The metal parts are made of copper, kovar, and iron, and are cylindrical with an outer diameter of 46 mm, an inner diameter of 44 mm, and a height of 20 mm. The metal parts were then pressed into the shape shown in Table 1. A 2 μm nickel plating was applied.
[0063] Next, the metal powder mixture ratio was 60:1 by weight of copper powder, tin powder, and titanium hydride (TiH) powder. Mix it with ethyl cellulose and terpineol to make a 30:10 ratio, and mix it in a kneader. The active metal brazing paste was prepared by sintering the ceramic parts. 100 mesh screen with outer diameter 48 mm x inner diameter 42 mm was used for screen printing. The active metal paste was printed to a thickness of 30 μm by inkjet printing and dried at 100°C in air. The ceramic parts on which the brazing paste was dried were heated in a nitrogen atmosphere continuous furnace at a temperature of (T1). By heating for 10 minutes or more, an active metal brazing material layer is formed on the end surface of the ceramic part. did.
[0064] Next, silver powder and copper powder were mixed in a metal powder ratio of 72:28 by weight to form an activated metal powder. The silver brazing paste was prepared by the same method as for the active metal brazing paste. The upper and lower ends (ring parts) of the ceramic part on which the filler layer was formed were fitted with a 48 mm outer diameter x 4 mm inner diameter. A 100μm thick wax layer was screen printed using a 2mm 100 mesh screen. The material paste was printed and dried at 100°C in air. Next, the metal parts, ceramic parts, The metal parts are placed on the jig in the correct order and heated in a hydrogen nitrogen atmosphere continuous furnace for 10 minutes or more at the heating temperature (T2). By heating for 10 minutes, the metal part and the ceramic part are joined to form a ceramic seal. The product was produced.
[0065] In addition, instead of metal parts, a 10mm x 100mm x 0.1mm test piece was used to measure the bonding strength. Using a metal plate, set the metal plate, ceramic parts, and metal plate in the order of the jig and press. The pieces were bonded by heating to prepare a test sample for bond strength.
[0066] [Table 1]
[0067] As can be seen from Table 1, in the embodiment, the heating temperature (T1), the brazing material printing thickness, the heating temperature (T 2), the temperature difference (T2-T1) was within the preferred range. It was outside the acceptable range.
[0068] Next, the ceramic sealing part is cut in the center as shown in Figure 2, and the joint is polished to remove the As shown in Figure 5, the central part is divided into 200 μm parts with a width (height) of 3.6 μm, and the energy distribution is The mass percentage of the constituent elements was measured using a diffuse X-ray fluorescence analyzer (WDX). Titanium, copper , silver, and each element are plotted on a graph like those in Figures 7 to 9, and the maximum value of active metal mass% ( Wm), the second maximum of active metal mass% (Wm2), the maximum of copper mass% (Wc), copper mass% The minimum value of silver (Wcl), the maximum value of silver mass% (Wa), and the silver content up to 1 / 4 of the ceramic part side Maximum mass% (Waq), range below 0.5Wc in copper mass% plot, silver mass The range of 0.5 Wa or less in the plot was obtained. From the obtained values, the active metal mass% The second maximum of the active metal mass% (Wm2 / Wm) for the maximum of the active metal mass% The minimum value of copper mass% (Wcl / Wc) and the maximum value of silver mass% on the ceramic part side The maximum value of silver mass% (Waq / Wa) up to 1 / 4 and copper mass% plot is 0.5 Calculate the percentage of the range below Wc and the percentage of the range below 0.5Wa in the plot of silver mass. The results are shown in Table 2.
[0069] [Table 3]
[0070] As can be seen from Table 2, the bonding strength of the embodiment is 6 The value was good, at 0 MPa or more. 、5 The bonding strength was 5 MPa or less. Under the bonding conditions of the examples, the ceramics and the active metal brazing material, the active metal brazing material and the brazing material, and the brazing material and the metal part reacted with each other to form a strong bonding layer. In contrast, under the bonding conditions of the comparative examples, the reaction did not proceed as much as in the examples, leading to a decrease in the bonding strength.
[0071] Next, the metal plate of the bonding strength test sample was bent at a right angle and pulled upward with an Instron tensile tester to determine the bonding strength. In addition, after the test, the upper part of the ceramic sealed part was held down with silicone applied to a circular jig made of Viton rubber, and the lower part was fixed to a helium leak detector and sucked in to perform a helium leak test. The helium leak test was performed in accordance with the vacuum spray method (spray method) of the "Helium Leak Test Method" (JIS Z2331:2006), and a leak rate of 1 x 10 at a vacuum of 1.3 μPa was obtained. -9 Pa·m 3 If no leakage of more than 1 / s occurred, it was rated as a pass (◯), and if leakage occurred, it was rated as a fail (×).
[0072] Furthermore, the ceramic sealed parts that passed the helium leak test were subjected to TCT (The Thermal Cycle Test: Temperature cycle test) at low temperature -40℃ x 30 minutes, high After 80 cycles of 125°C x 30 minutes, a helium leak test was performed. When no leakage occurred, it was judged as pass (◯), and when leakage occurred, it was judged as fail (×). The test results for each of the comparative examples are shown in Table 3.
[0073] [Table 3]
[0074] As can be seen from Table 2, the bonding strength of the examples was a good value of 0.60 MPa or more. In contrast, in the comparative example, the pressure was 0.55 MPa or less. The solder and the active metal brazing material, the active metal brazing material and the brazing material, and the brazing material and the metal part are reacted with each other. In contrast, under the bonding conditions of the comparative example, The reaction did not proceed as expected, leading to a decrease in the bonding strength.
[0075] In addition, the ceramic sealing parts according to the embodiment did not cause any leak failures in the helium leak test. This was because the joining distance was sufficient for the ceramic and metal parts. The bonding strength is ensured by the bonding layer consisting of the active metal brazing material layer and the brazing material layer. This is because the difference in thermal expansion was reduced. In contrast, a leak defect occurred in the comparative example. This was due to the fact that the bonding strength was not high enough and the difference in thermal expansion between the ceramic and metal parts. This was because there was damage to the joints and they were no longer airtight.
[0076] In addition, the ceramic sealed parts according to the embodiment did not leak in the helium leak test after TCT. This is because the joining distance for ceramic and metal parts is not sufficient. In addition, the bonding strength is ensured by the bonding layer consisting of the active metal brazing material layer and the brazing material layer. The low bonding temperature and the thermal stress caused by heating and cooling prevent damage to the bonding layer. In contrast, in the comparative example, the helium leak failure after TCT was This is because the bonding strength of the bonding layer consisting of the active metal brazing material layer and the brazing material layer is not sufficiently secured. In addition, the thermal expansion difference was not sufficiently alleviated, so the joints were damaged by the thermal stress caused by heating and cooling. This was because the bonding layer was damaged, creating a leak path.
[0077] As is clear from the results shown above, the examples have improved leak characteristics and TCT compared to the comparative examples. An improvement in reliability was observed.
[0078] Although several embodiments of the present invention have been illustrated above, these embodiments are presented as examples. These novel embodiments are not intended to limit the scope of the invention. It is possible to implement the present invention in various other forms, and various modifications are possible without departing from the spirit and scope of the present invention. Various omissions, substitutions, modifications, etc. may be made. The scope of the invention and its equivalents as described in the claims are included in the scope and spirit of the disclosure. In addition, the above-described embodiments can be implemented in combination with each other. [Explanation of symbols]
[0079] 1...Ceramics sealing parts 2. Metal parts 3. Ceramic parts 4…Active metal brazing layer 5…Brazing layer 6…Brazing paste
Claims
1. In a ceramic sealed component in which a ceramic part and a metal part are bonded with a bonding layer containing silver, copper, and an active metal, Silver and copper are molten in the bonding layer, When the cross section of the central portion of the bonding layer is divided into 20 or more layers, the mass percentages of silver, copper, and active metal are measured, and the mass percentages are plotted from the ceramic component side to the metal component side of the bonding layer, there is a maximum value of the active metal mass percentage (Wm), a maximum value of the copper mass percentage (Wc), and a maximum value of the silver mass percentage (Wa), A ceramic sealed component, characterized in that the second largest maximum value of the active metal mass% is 0.7 times or less the maximum value (Wm), the minimum value of the copper mass% is 0.3 times or more the maximum value (Wc), and the maximum value of the silver mass% up to a distance of 1 / 4 of the ceramic component side is 0.3 to 0.5 times the maximum value (Wa).
2. 2. The ceramic sealing part according to claim 1, wherein in the plot of copper mass %, the range of 0.5Wc or less is 40% or less, and in the plot of silver mass %, the range of 0.5Wa or less is 50% or less.
3. 3. The ceramic sealed part according to claim 1, wherein the active metal brazing material is one or more active metals selected from titanium, zirconium and hafnium, and one or more brazing metals selected from copper and silver.
4. 3. The ceramic sealed part according to claim 1, wherein the thickness of the bonding layer is 70 [mu]m or more.
5. 3. The ceramic sealed part according to claim 1, wherein the metal part is one or more metal parts selected from the group consisting of iron, iron alloys, iron-nickel alloys, copper and copper alloys.
6. 3. The ceramics sealing part according to claim 1, wherein the ceramics part is made of alumina, aluminum nitride, silicon nitride or alumina.
7. A method for manufacturing a ceramic sealed part that joins a ceramic part and a metal part, comprising the steps of: printing and drying a paste made of an active metal brazing material containing copper on an end surface of the ceramic part, and heating the printed paste at a heating temperature (T1) of 800°C or less to form an active metal brazing material layer on the end surface of the ceramic part; printing and drying a paste made of a brazing material containing silver so as to cover the entire surface of the formed active metal brazing material layer; placing the metal part on the ceramic part and heating the printed paste at a temperature (T2) of 820°C or less to form a brazing material layer; and joining the ceramic part and the metal part with a heating temperature difference (T2-T1) of 20°C or more.
8. A method for manufacturing a ceramic sealed part as described in claim 7, characterized in that the active metal brazing material is one or more active metals selected from titanium, zirconium and hafnium, and one or more brazing material metals selected from copper and silver.
9. 9. The method for producing a ceramic sealed part according to claim 7, wherein the printing thickness of the paste made of the active metal brazing material is 20 μm or more, and the printing thickness of the paste made of the silver-containing brazing material is 50 μm or more.
10. The method for manufacturing a ceramic sealed part according to claim 7 or 8, characterized in that the metal part is one or more metal parts selected from iron, iron alloys, iron-nickel alloys, copper and copper alloys.
Citation Information
Patent Citations
Semiconductor device
JP1989046978A
Composite ceramic substrate
JP1997121004A
Ceramics-metal composite circuit board
JP1997283671A
Metal-ceramic bonded material and method for producing the same
JP2001220253A
Metal-ceramic bonded substrate, manufacturing method thereof, and brazing material
JP2023006077A